2019
DOI: 10.1101/629873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the performance of 3-tissue constrained spherical deconvolution pipelines for within-tumor tractography

Abstract: The use of diffusion MRI (dMRI) for assisting in the planning of neurosurgery has become increasingly common practice, allowing to non-invasively map white matter pathways via tractography techniques. Limitations of earlier pipelines based on the diffusion tensor imaging (DTI) model have since been revealed and improvements were made possible by constrained spherical deconvolution (CSD) pipelines. CSD allows to resolve a full white matter (WM) fiber orientation distribution (FOD), which can describe so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Finally, we upsampled the preprocessed data to 1.3⨉1.3⨉1.3mm 3 isotropic voxels (Greenspan, 2008;Kuklisova-Murgasova et al, 2012;Bastiani et al, 2019). These preprocessing steps are largely similar to those used in other recently published works (Bastiani et al, 2019;Pietsch et al, 2019;Mito et al, 2019;Aerts et al, 2019). Brain masks were obtained for all subjects by performing a recursive application of the Brain Extraction Tool (Avants et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we upsampled the preprocessed data to 1.3⨉1.3⨉1.3mm 3 isotropic voxels (Greenspan, 2008;Kuklisova-Murgasova et al, 2012;Bastiani et al, 2019). These preprocessing steps are largely similar to those used in other recently published works (Bastiani et al, 2019;Pietsch et al, 2019;Mito et al, 2019;Aerts et al, 2019). Brain masks were obtained for all subjects by performing a recursive application of the Brain Extraction Tool (Avants et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Even for WM tractography in cases of infiltration by pathological tissues, the 3-tissue CSD approach can provide direct benefits in terms of recovering healthy WM structures, e.g. in infiltrating tumors (Aerts et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the resulting white matter fiber orientation distributions (FODs), probabilistic streamlines tractography was performed, using an FOD amplitude threshold of 0.07 (Tournier, Calamante, & Connelly, 2010). Although white matter FODs could be estimated using SS3T-CSD within regions infiltrated by a tumor (Aerts et al, 2019), resulting white matter FOD amplitudes were substantially smaller in tumor regions compared to the rest of the brain. While this likely reflects the smaller portion of space taken up by axons (due to infiltrating tumor tissue) and/or damage to white matter tracts, it does pose a practical challenge to tractography algorithms, which rely on the aforementioned amplitude threshold to determine where and how far tractography may proceed.…”
Section: Reconstruction Of Pre-operative Tumor Structural Connectomementioning
confidence: 99%
“…Starting from the preprocessed pre-operative dMRI data, a novel technique to model the diffusion signal was applied, named single-shell 3-tissue constrained spherical deconvolution (SS3T-CSD) Dhollander, Raffelt, & Connelly, 2016), using MRtrix3Tissue (https://3Tissue.github.io), a fork of the MRtrix3 software (Tournier et al, 2019). Investigating the performance of this technique for this purpose, we have recently shown that SS3T-CSD allows to reconstruct white matter streamlines within infiltrative tumors and in immediately adjacent tissue (Aerts, Dhollander, & Marinazzo, 2019).…”
Section: Reconstruction Of Pre-operative Tumor Structural Connectomementioning
confidence: 99%
See 1 more Smart Citation